Quantification of Phenolic Compounds and In Vitro Radical Scavenging Abilities with Leaf Extracts from Two Varieties of Psidium guajava L. - Julio César Camarena-Tello; Héctor Eduardo Martínez-Flores; Ma. Guadalupe Garnica-Romo; José Saúl Padilla-Ramírez; Alfredo Saavedra-Molina; Osvaldo Alvarez-Cortes; María Carmen Bartolomé-Camacho; José Octavio Rodiles-López (MDPI AG, 2018)
Guava leaf (Psidium guajava L.) extracts are used in both traditional medicine and the pharmaceutical industry. The antioxidant compounds in P. guajava leaves can have positive effects including anti-inflammatory, anti-hyperglycemic, hepatoprotective, analgesic, anti-cancer effects, as well as protecting against cardiovascular diseases. In the present study, phenolic compounds and in vitro antioxidant capacity were measured in extracts obtained with polar and non-polar solvents from leaves of two varieties of guava, Calvillo Siglo XXI and Hidrozac. The quantity of total phenolics and total flavonoids were expressed as equivalents of gallic acid and quercetin, respectively. Hydroxyl radical, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and Oxygen Radical Absorbance Capacity using fluorescein (ORAC-FL) in vitro tests were used to assess the radical scavenging abilities of the extracts. The total phenolics were higher in the aqueous fraction of the variety Calvillo Siglo XXI, while in the Hidrozac variety total phenolics were higher in the acetone and chloroform fractions. Total flavonoids were higher in all fractions in the variety Calvillo Siglo XXI. Total phenolics showed a highly positive correlation for ORAC-FL, and a moderately positive correlation with hydroxyl radicals. Finally, total flavonoids showed a slightly positive correlation for ORAC-FL and hydroxyl radicals. Both varieties of guava leaf extract showed excellent antioxidant properties.